2014
DOI: 10.1088/1674-1056/23/4/040203
|View full text |Cite
|
Sign up to set email alerts
|

A meshless method based on moving Kriging interpolation for a two-dimensional time-fractional diffusion equation

Abstract: Fractional diffusion equations have been the focus of modeling problems in hydrology, biology, viscoelasticity, physics, engineering, and other areas of applications. In this paper, a meshfree method based on the moving Kriging interpolation is developed for a two-dimensional time-fractional diffusion equation. The shape function and its derivatives are obtained by the moving Kriging interpolation technique. For possessing the Kronecker delta property, this technique is very efficient in imposing the essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Jiang and Qi [28] derived a fractional thermal wave model of skin burns caused by spatial heating. The multi-term time-space fractional advection-diffusion equations on a finite domain were considered and the analytical solutions were derived by Jiang et al [29] The numerical methods of solving the diffusion equations have also been studied, such as the meshless method [30][31][32] and the numerical inverse Laplace transform method. [33] Some research on the fractional Cattaneo model and its applications can be found in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang and Qi [28] derived a fractional thermal wave model of skin burns caused by spatial heating. The multi-term time-space fractional advection-diffusion equations on a finite domain were considered and the analytical solutions were derived by Jiang et al [29] The numerical methods of solving the diffusion equations have also been studied, such as the meshless method [30][31][32] and the numerical inverse Laplace transform method. [33] Some research on the fractional Cattaneo model and its applications can be found in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…, B n+1 forms a basis for functions defined over the problem domain [a, b]. The exponential B-splines (4) and their first and second derivatives vanish outside the interval…”
Section: Spatial Discretizationmentioning
confidence: 99%
“…Recently, interest in fractional calculus has experienced rapid growth and we can find many papers about its theory and applications in mathematics, physics, mechanics, information engineering, electronic engineering, and control engineering. [10][11][12][13][14][15][16][17] As for the controllability of a fractional order dynamical system, there are some published papers. [18][19][20] However, we cannot find any contribution to the controllability of fractional order circuits, to our best knowledge, although it is also an important research field.…”
Section: Introductionmentioning
confidence: 99%